Modulation of the Transmission Spectra of the Double-Ring Structure by Surface Plasmonic Polaritons. (15th April 2021) - Lai, Senfeng; Guo, Yanpei; Liu, Guiyang; Shan, Chun; Huang, Lixin; Zhang, Yicong; Wu, Yanghui; Gu, Wenhua; Wu, Wen
Abstract : This paper proposes a new structural design to excite surface plasmonic polaritons to enhance the double-ring interference structure. The double-ring structure was etched into a thin film to form fundamental interference patterns, and periodic concentric-ring grooves were employed to gather energy from the surrounding regions through the excitation of surface plasmonic polaritons. Accordingly, the energy of the incident light can be concentrated at the center. The surface plasmon modulates the interference pattern and the transmission spectra. The transmission peak position and its intensity can be tuned by changing the alignment of the grooves. The proposed structure can be applied for designing plasmonic devices as useful components of the plasmonic toolbox.